THE EFFECT OF ADDITIONIN DIFFERENT FISH MEAL DOSES ON GROWTH AND SURVIVALRATE OF CACHAMA FISH (Colossoma macropomum) USING BIOFLOCK SYSTEM IN SALIN WATER - Fitri Rahmadani; Iskandar Putra; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK            The aim of the research was to determine the effect of different fish meal doses on the growth and survival rate of cachama fish (Colossoma macropomum) using the biofloc system in salin water. This research was conducted for 40 days from February 23 to April 3, 2019, which took place in the Technical Service Unit (UPT) Pool and Hatchery of the Faculty of Fisheries and Marine University of Riau. This research was using the experimental method by completely random design (RAL) one factor with three replications. The treatments were 2% feed dosage from fish biomass weight, 3% feed dose from fish biomass weight, 4% feed dose from fish biomass weight, and 5% feed dose from fish biomass weight. To minimize the error of each treatment level, repeated 3 times. The material used for biofloc technology is multi-cell probiotics, molasses and sea water which are diluted to 6 ppt. The results showed that the different feed doses to the maintenance of cachama fishwith biofloc systems in salin water affected the growth and survival of  cachama fish. In addition, it also affects the daily growth rate, feeds efficiency and feeds conversion ratio. The optimal doses is found in treatment P4 (5% feed doses) resulting in an absolute growth of 8.64 g, growth of an average length of 8.51 cm, the specific growth rate of 4.9%, the survival rate was 100%, feed efficiency was 112.4 % and feed conversion ratio was 0.9. Keywords: Biofloc, cachama fish, feeds, 6 salinity